2021
DOI: 10.1002/adhm.202100008
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Immunotherapy with Micellar Resiquimod–Polymer Conjugates Triggers a Robust Antitumor Response in a Breast Cancer Model

Abstract: Resiquimod is an immunopotent toll-like receptor 7/8 agonist with antitumor activity. Despite being potent against skin cancers, it is poorly tolerated systemically due to toxicity. Integrating resiquimod into nanoparticles presents an avenue to circumvent the toxicity problem. Herein, the preparation of degradable nanoparticles with covalently bound resiquimod and their systemic application in cancer immunotherapy is reported. Dispersion in water of amphiphilic constructs integrating resiquimod covalently bou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 73 publications
2
13
0
Order By: Relevance
“…In the present study, we utilized 4 mg/kg R848 NE and 2 mg/kg SD-101 individually or in combination to show a synergized antitumor efficacy through intraperitoneal administration. The moderate antitumor efficacies by R848 NE and SD-101 individual treatments were observed (Figure 5C,D,F) compared with saline control (Figure 5B), which correspond with the previous studies for R848 and SD-101 [58,59]. Although individual treatments of R848 NE or SD-101 showed significant tumor growth inhibition (TGI) (50.72% ± 16.83% and 65.65% ± 12.88%), R848 NE/SD-101 combination treatment reached approximately 84.62% ± 28.05% total tumor growth inhibition at the end of the study (Table 1) with the median tumor growth inhibition of 98.05% (Table S3), suggesting the synergistic antitumor efficacy carried out by R848 NE/SD-101 combination treatment.…”
Section: In Vivo Antitumor Efficacysupporting
confidence: 90%
See 1 more Smart Citation
“…In the present study, we utilized 4 mg/kg R848 NE and 2 mg/kg SD-101 individually or in combination to show a synergized antitumor efficacy through intraperitoneal administration. The moderate antitumor efficacies by R848 NE and SD-101 individual treatments were observed (Figure 5C,D,F) compared with saline control (Figure 5B), which correspond with the previous studies for R848 and SD-101 [58,59]. Although individual treatments of R848 NE or SD-101 showed significant tumor growth inhibition (TGI) (50.72% ± 16.83% and 65.65% ± 12.88%), R848 NE/SD-101 combination treatment reached approximately 84.62% ± 28.05% total tumor growth inhibition at the end of the study (Table 1) with the median tumor growth inhibition of 98.05% (Table S3), suggesting the synergistic antitumor efficacy carried out by R848 NE/SD-101 combination treatment.…”
Section: In Vivo Antitumor Efficacysupporting
confidence: 90%
“…In the present study, we utilized 4 mg/kg R848 NE and 2 mg/kg SD-101 individually or in combination to show a synergized antitumor efficacy through intraperitoneal administration. The moderate antitumor efficacies by R848 NE and SD-101 individual treatments were observed (Figure 5C,D,F) compared with saline control (Figure 5B), which correspond with the previous studies for R848 and SD-101 [58,59]. Several reports indicated that both TLR7/8 and TLR9 stimulate IL-6 production, which acts as both a pro-inflammatory and anti-inflammatory cytokine [44][45][46][47].…”
Section: In Vivo Antitumor Efficacysupporting
confidence: 89%
“…13a). 136 Resiquimod was covalently bound to a biodegradable polymer via hydrolytically degradable ester links between the agonist and the polymer, and the size of the NPs was modulated to less than 20 nm which could greatly enhance the permeation and accumulation in the lymphatic system where APCs are present in large quantities and the metastasis usually occurs. After being accepted by cells, the ester links were cleaved quickly probably due to the enzymatic activity and acid condition, releasing resiquimod (Fig.…”
Section: Biodegradable Materials Used In Cancer Therapymentioning
confidence: 99%
“…Several advanced therapeutic drugs, including immune-activating, small molecule targeted, and antibody drugs, have been successful in other malignant tumors. [7][8][9] Unfortunately, the blood-brain barrier (BBB) and blood-brain-tumor barrier (BBTB) restrict the current drugs from entering the brain for effective GBM treatment. 10 Therefore, many therapeutic agents that are effective against glioma cells in vitro exhibit lower response in vivo.…”
Section: Introductionmentioning
confidence: 99%